Thinking Global and Sounding Local: the Case of Kajkavian: Repertoire in the Production of Edison Bell Penkala in the 1920s and 1930s - Tanja Halužan (Arti Musices, 2022)
This paper presents initial findings in the research on the status of Kajkavian repertoire primarily in the production of Edison Bell Penkala. From its beginning in 1927, this Zagreb based record company engaged local authors and performers. A significant part of this production consisted of repertoire in the Kajkavian dialect group of the Croatian language which, from the mid-nineteenth century, was an arena of debate on local versus ethno-national affiliations, related also to the issue of the standardization of language. Considering particularly the matter of locality which arose as a key concept for interpreting the underpinnings of the record industry of the time, I aim to delineate the status of Kajkavian repertoire within the company’s overall production, as well as its consequences for the formation of representative regional repertoire.